New Frontiers for Museum Spaces in the Phygital Dimension:: What Digital Technology Can Do - Miano, Alessandra (Mimesis Journal, 2024)
The article explores the transformation of the design of the museum experience, focusing on the centrality of the dialect between tangible and intangible and the interweaving of the digital layer into the phygital scenario. In this transformation, digital technology plays a central role, superimposing as a subtle, narrative, and interactive layer, activated by the bodily gestures as intimate appropriation of the space and the artworks on display. The digital becomes phygital, conceived as a simultaneous overlapping of real and digital, enhancing narrative processes staged in a museum space embodied by the dynamic movements of the visitors.